Intra‐Operative Cholangiography With Indocyanine Green Used to Assess Bile Duct Patency in a Dog With a Ruptured Gallbladder Mucocele - Yujin Kim; Sungin Lee (Veterinary Medicine and Science, 2025)
ABSTRACT In human laparoscopic hepatobiliary surgery, near‐infrared fluorescence (NIRF) indocyanine green (ICG) is commonly employed for intraoperative cholangiography to delineate anatomical structures; however, it is not yet used in veterinary medicine. This is the first veterinary case of ICG cholangiography used to confirm common bile duct (CBD) patency in a dog with a ruptured gallbladder mucocele (GBM). A 10‐year‐old female dog presented with lethargy and anorexia. Blood analysis revealed increased ALT, ALP, GGT, total bilirubin and C‐reactive protein levels. Ultrasonography revealed a ruptured GBM. To evaluate CBD patency during surgery, ICG 0.05 mg/kg was injected intravenously 3 h preoperatively. During cholecystectomy, real‐time NIRF image of ICG in the CBD showed a filling defect, indicating a partial obstruction within the lumen. After gentle massaging manipulation, CBD patency was confirmed using the NIRF image. No catheterisation or flushing of the CBD was required. The patient showed no relevant clinical signs of biliary stasis 5 months post‐surgery. Intraoperative ICG cholangiography efficiently and easily assessed CBD patency in real‐time. In this case, CBD patency was achieved by external manipulation with the surgeon's fingers. Therefore, catheterisation or flushing was not necessary. Since enterotomy or cholecystectomy was unnecessary, complications from the leakage of intestinal content or bile were avoided.